Validation of a System to Predict Recanalization After Endovascular Treatment of Intracranial Aneurysms. Issue 2 (4th April 2015) - Ogilvy, Christopher S.; Chua, Michelle H.; Fusco, Matthew R.; Griessenauer, Christoph J.; Harrigan, Mark R.; Sonig, Ashish; Siddiqui, Adnan H.; Levy, Elad I.; Snyder, Kenneth; Avery, Michael; Mitha, Alim; Shores, Jorma; et al.
Abstract: BACKGROUND: With increasing use of endovascular techniques in the treatment of ruptured and unruptured aneurysms, the issue of obliteration efficacy has become increasingly important. We have previously reported the Aneurysm Recanalization Stratification Scale, which uses accessible predictors including aneurysm-specific factors (size, rupture, and intraluminal thrombosis) and treatment-related features (treatment modality and immediate angiographic result) to predict retreatment risk after endovascular therapy. OBJECTIVE: To assess the external validity of the Aneurysm Recanalization Stratification Scale. METHODS: External validity was assessed in independent cohorts from 4 centers in the United States and Canada where endovascular and open neurovascular procedures are performed, and in a multicenter cohort of 1543 patients. Probability of retreatment stratified by risk score was derived for each center and the combined multicenter cohort. RESULTS: Despite moderate variability in retreatment rate among centers (29.5%, 9.9%, 9.6%, 26.3%, 19.7%, and 18.3%), the Aneurysm Recanalization Stratification Scale demonstrated good predictive value with C-statistics of 0.799, 0.943, 0.780, 0.695, 0.755, and 0.719 for each center and the combined cohort, respectively. Probability of retreatment stratified by risk score for the combined cohort is as follows: −2, 4.9%; −1, 5.7%; 0, 5.8%; 1, 13.1%; 2, 19.2%; 3, 34.9%; 4, 32.7%; 5, 73.2%; 6, 89.5%; and 7, 100.0%. CONCLUSION: Surgical decision-making and patient-centered informed consent require comprehensive and accessible information on treatment efficacy. The Aneurysm Recanalization Stratification Scale is a valid prognostic index. This is the first comprehensive model that has been developed to quantitatively predict retreatment risk following endovascular therapy.